THE REVIEW OF THE NAME AND NATURE OF TRANSLATION SCIENCE - Sheraliyeva, Shaxnoza (Журнал иностранных языков и лингвистики, 2023)
In our article, the name and type of translation science are relevant to what extent they are relevant in the current period of development, and the seminal article in the development of translation science is considered as a historical document testifying to the state of this discipline in the early days. Their impact can be seen through inclusion in translation-based anthologies, introductory texts, and manuals.